TV and educating university youth about the challenges of cultural identity in Iraq Field study of a sample of students at University of Baghdad - Hamoudi, Safad Hussam; Mustaf, Adel Adbulrazaq (ALBAHITH ALALAMI, 2014)
The TV plays an active role in building the general culture of the recipients, which calls for emphasizing its contemporary mission in rebuilding the values that support the development and modernization of diverse societies. Such importance is necessary to explore the challenges facing the cultural invasion, The space opening, which had its cultural returns to the societies, produced a space for alternative values and antagonisms in the cultures and traditions of these societies in the midst of a psychological / social conflict behind a clash with the peculiarities of Muslim societies. Cultural Adtha.From these points of view, and because the universities are an important stage to announce the demands of the advocates of change and to reach the demands in diverse societies, who are constantly seeking to open channels of communication with the students of these universities to support them and to launch them to the street for political, cultural, social and even psychological factors. Several of our motivations are to study the role of television in Iraq in addressing the cultural challenges that have become a threat to the cultural and Islamic identity of the society in general and the youth in particular. To raise awareness of the dangers of this cultural invasion on the specificities of their identity.